Forest‐cutting rapidly improves the demographic status of Paeonia officinalis, a species threatened by forest closure. Issue 1 (19th October 2012) - Andrieu, Emilie; Fréville, Hélène; Besnard, Aurélien; Vaudey, Valentine; Gauthier, Perrine; Thompson, John D.; Debussche, Max
Abstract: In the Mediterranean region, the spread and densification of woodlands and shrublands subsequent to rural depopulation is a critical issue for the conservation of open‐habitat plant species. Our objective was to assess the effectiveness of forest management to reduce the negative impact of forest closure on the persistence of a protected herbaceous perennial species Paeonia officinalis . Using demographic surveys from 2003 to 2008 in a woodland, open and managed habitat clear‐cutted for the aim of our study, we assessed the effect of forest opening on plant performance and population dynamics. In addition, we performed a shading experiment on reproductive plants to mimic canopy closure and study its impact on plant growth and fecundity. Based on quadrat surveys and matrix models, we showed that forest cutting induced a rapid increase in plant performance and population asymptotic growth rate. Indeed, within 2 years, plant size, flower, seed and ovule numbers as well as the plant stage distribution, asymptotic growth rates and elasticity patterns shifted from values similar to those in the woodland habitat to values similar to those in the open habitat. Similarly, artificially shaded reproductive plants regressed within 2 years towards the vegetative stage. For perennial plants which have a stage in their life‐cycle which allows for individual survival under unfavourable conditions such as the vegetative stage for P. officinalis, such demographic plasticity may be fundamental for their long‐term persistence in temporally heterogeneous environments. Our study highlights the need to mix an experimental approach with a mid‐term demographic survey in order to design efficient conservation management strategies for declining populations of rare species.